2017
DOI: 10.4103/ija.ija_285_17
|View full text |Cite
|
Sign up to set email alerts
|

A cohort evaluation of clinical use and performance characteristics of Ambu® AuraGain™: A prospective observational study

Abstract: Background and Aims:Ambu® AuraGain™ (AG) (Ambu, Ballerup, Denmark) is a supraglottic device which has a design facilitating its use as a conduit for intubation. We designed this prospective observational study to assess the ease of AG placement in paralysed patients, determine its position and alignment to the glottis and assess its utility as a conduit for intubation.Methods:One hundred patients, aged 18–60 years, American Society of Anesthesiologists physical status I–II, undergoing elective surgery under ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…In another study of 100 patients, optimal visualisation was obtained in 68% of the patients and 84% were successfully intubated using the AuraGain™ for FIB. 18 These findings are similar to our results. In another study, three experienced anaesthesiologists performed awake FBI through an i-gel™.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In another study of 100 patients, optimal visualisation was obtained in 68% of the patients and 84% were successfully intubated using the AuraGain™ for FIB. 18 These findings are similar to our results. In another study, three experienced anaesthesiologists performed awake FBI through an i-gel™.…”
Section: Discussionsupporting
confidence: 93%
“…Further, only one anaesthesiologist performed airway management. In another study of 100 patients, optimal visualisation was obtained in 68% of the patients and 84% were successfully intubated using the AuraGain™ for FIB 18 . These findings are similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…[ 6 ] Studies in the adult population using Ambu Aura gain for airway control revealed a much higher OSP. [ 7 8 9 ] The higher seal pressures in adult patients probably reflect a difference in their anatomy with the pediatric airway. However, the OSP of Ambu AuraGain™ was comparable to that of other SADs such as i-gel, LMA ProSeal, and LMA Supreme, as reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Success rate of intubation in clinical practice may be lower than that found in a manikin study, as seen in a study by Parikh et al . [ 30 ] evaluating performance of LSFOI through AmbuAuragain in paralysed patients whose airways were not anticipated to be difficult. They found that 5 out of 100 patients could not be intubated, while our manikin study had a 100% intubation success rate with AmbuAuragain.…”
Section: Discussionmentioning
confidence: 99%